Contributions of creative outputs to economic growth: A disaggregated analysis - Rajeev K. Goel (Managerial and Decision Economics, 2022)
This paper studies contributions of creative outputs to economic growth across a sample of 131 nations. Results show that the contributions of overall creative outputs to economic growth are statistically insignificant; however, upon disaggregation, creative goods and services show positive growth dividends, especially in 5-year growth. In contrast, growth returns from capital formation are more immediate, while those from labor are diffused. ISO quality certifications showed positive growth effects. When contributions of creative goods were examined across nations with different growth rates, creative goods and services positively contributed to 5-year growth in median growth nations, but not elsewhere.
Keywords: O47; O43; O50; 330; economic growth; creative outputs; creative goods; intangible assets; online creativity; ISO certification